Gastrointestinal hormones and the gut connectome. Issue 1 (February 2017) - Ye, Lihua; Liddle, Rodger A.
Abstract : Purpose of review: Provision of adequate nutrients by the gut is essential for survival and essential behaviors are linked to the proper ingestion and digestion of food. Recently, a new neural connection has been reported between sensory cells of the gut epithelium and the nervous system that mediates signals from the gut to the brain. Recent findings: This review describes how the gut senses its environment, relays those signals to the brain, and how the brain influences the gut. Summary: This gut–brain connection provides a pathway for how the body handles food.